From Hair-Pulling to Trichobezoars and Rapunzel Syndrome: A Comprehensive Review of Trichotillomania - Rosińska Kamila; Julia Natalia Łojewska; Ewelina Justyna Janicka; Agnieszka Perko; Mateusz Rosiński; Monika Niedźwiedzka; Oliwia Bochenek; Mateusz Koper (Nicolaus Copernicus University in Toruń, 2024)
Introduction: Trichotillomania (TTM) is an obsessive-compulsive disorder characterized by the uncontrollable pulling of hair from various parts of the body, most commonly from the scalp, eyebrows, and eyelashes. Clinical manifestations of TTM include patchy alopecia, uneven hair shaft growth, and characteristic changes visible in trichoscopy, such as the presence of black dots, twisted hairs, split ends, and hairs shaped like exclamation marks. The etiology of TTM is complex and involves genetic, neurological, and psychological factors. In some patients, TTM co-occurs with trichophagia, leading to the formation of trichobezoars in the gastrointestinal tract. In extreme cases, such as Rapunzel Syndrome, bezoars can lead to intestinal obstruction. Treatment for TTM is multifaceted and includes both psychotherapeutic and pharmacological interventions. Objective: The objective of this study is to provide a comprehensive review of trichotillomania (TTM), with a particular focus on its clinical symptoms, etiology, diagnostics, and treatment methods. The aim is to understand this obsessive-compulsive disorder, its impact on patients' lives, and its connections to serious complications such as trichobezoars and Rapunzel Syndrome. Materials and Methods: The study utilized analyses of scientific research, review articles, and reports concerning trichotillomania (TTM), trichobezoars, trichophagia, and Rapunzel Syndrome. It is primarily based on data from PubMed, Google Scholar, Cochrane Library, and studies published between 2000 and 2024, focusing on the diagnostics, etiology, and treatment of TTM and related disorders. Conclusions: The purpose of this study is to provide a comprehensive review of the current knowledge on trichotillomania, including its clinical symptoms, etiology, diagnostics, and treatment methods, while considering serious complications such as trichobezoars and Rapunzel Syndrome.